Предмет:
МатематикаАвтор:
анонимПредставим выражения в виде степени:
а) у³ : у⁵ = y^3/y^5 = y^(3 - 5) = y^(-2);
В итоге получили, у³ : у⁵ = y^(-2).
б) m⁵ × (m²)³/(m⁷ × (m²)²) = m^5 * m^(2 * 3)/(m^7 * m^(2 * 2)) = m^5 * m^6/(m^7 * m^4) = m^5 * m^6/m^(7 + 4) = m^(5 + 6)/m^(7 + 4) = m^11/m^11 = m^(11 - 11) = n^0 = 1.
В итоге получили, m⁵ × (m²)³/(m⁷ × (m²)²) = 1.
Автор:
maverick28Добавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть